A monoclonal antibody to the interleukin-2 receptor enhances the survival of neural allografts: a time-course study. - Wood, M; Sloan, D; Dallman, M; Charlton, H (1992)
A time-course study of the survival and immunological characteristics of rat neural allografts was undertaken in animals treated with a murine monoclonal antibody to the alpha-chain (p55) of the rat interleukin-2 receptor. This antibody, NDS 63, was administered for ten days following grafting beginning on the day of operation. Inbred rat strains differing at both major and minor histocompatibility loci were selected as donor and host. Furthermore, the recipient strain displayed a high responder major histocompatibility complex haplotype. All grafts were placed in the lateral ventricle. Comparison was drawn between NDS 63-treated recipients and two groups of controls; an untreated group and a second group treated with the monoclonal antibody NDS 66, directed at a second epitope on the alpha-chain of the interleukin-2 receptor, which has been shown to be ineffective in competing with interleukin-2 for binding. Immunocytochemical analysis of the transplants was performed at several time-points up to 150 days following grafting. Grafts of NDS 63-treated recipients exhibited 100% survival with minimal induction of major histocompatibility complex antigens (both class I and class II) and negligible leukocyte infiltration at all time-points studied. In contrast grafts from both groups of controls showed evidence of a chronic immune response with most grafts undergoing rejection as shown by markedly elevated major histocompatibility complex antigen expression accompanied by specific immune cell infiltration. This was a protracted process with several grafts undergoing complete rejection by 60 days and a majority, but not all, by 150 days after transplantation. It is concluded that NDS 63, a monoclonal antibody to the interleukin-2 receptor, may diminish the immune response to transplanted allogeneic neural tissue and thereby enhance its prospects for long-term survival.